Analyse the Factors Influencing Dividend Decisions: A Conceptual Analysis of Dividend Policy and its Impact on Firm Performance (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Dividend policy has attracted greater attention at the global level over the last decade as it has significant effect on the performance of a form or company enhancing the degree of attention worldwide. It has been considered as the most imperative financial decisions as per the consumers, employees, regulatory bodies and Government point of view. Dividend policy is very significant in managing the earnings of a firm or company hence the decisions regarding the dividend policy have direct impact on the firm’s credit standing, its share prices and the future growth in the business world. This conceptual paper researcher analyse the theories of dividend policy and factors affecting the dividend decisions.